Effect of Temperature on the Binding and Distribution Characteristics of Thionine in Sodium Dodecylsulfate Micelles - CANTÜRK TALMAN, REMZİYE YEŞİM; GÖKTÜRK, SİNEM (SPRINGER/PLENUM PUBLISHERS, 2008)
The interaction between thionine (a cationic thiazine dye) and anionic surfactant sodium dodecylsulfate in aqueous solution at different temperatures has been studied spectrophotometrically. The absorption spectra were used to quantify the dye/surfactant binding constants and surfactant/water partition coefficients of the dye by applying mathematical models that consider partitioning of the dye between the micellar and aqueous pseudo-phases. The Benesi-Hildebrand equation was applied to calculate the binding constants of thionine to sodium dodecylsulfate micelles over a temperature range of 293 to 333 K. To evaluate the thermodynamic aspects of the interaction of thionine with sodium dodecylsulfate micelles, Gibbs energy, enthalpy and entropy changes were determined. The effect of temperature on the critical micelle concentration of sodium dodecylsulfate in the presence of thionine was also studied and discussed. The binding affinity of thionine to the sodium dodecylsulfate micelles significantly decreased with increasing temperature because of the thermal agitation.
Keywords: Dye-surfactant interactions; Thermodynamics; Thionine; Sodium dodecylsulfate; Spectrophotometry; Binding constant; Partition coefficient; Critical micelle concentration; DYE-SURFACTANT INTERACTION; CATIONIC SURFACTANT; CETYLPYRIDINIUM CHLORIDE; ANIONIC SURFACTANT; AQUEOUS-SOLUTIONS; ALKYL SULFATES; THERMODYNAMICS; WATER; SYSTEMS; ACID